More R&D, less growth? China's decreasing research productivity in international comparison - Philipp Boeing; Paul Hünermund (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Innovation is widely considered the primary driver of growth in high-income economies. The efficiency by which an economy is able to transform research & development (R&D) inputs into output growth is captured by the measure of research productivity. In a recent study we were able to show that research productivity is declining over time, not just in the U.S., which has been shown before, but also in China and Germany. This implies that new ideas and innovations are universally harder to find. In Germany, business R&D spending has increased by an average of approximately 3.3% per year during the last three decades. At the same time, research productivity has fallen on average by 5.2% per year, which is very similar to the estimates obtained for the U.S. In China, we observe a substantial expansion of research activities during the first and second decade of this century, indicated by a growth rate of 21.9% in research spending. The resulting output growth, however, is not proportional to such inputs, which is reflected by a 23.8% decrease in estimated research productivity, or a reduction by half in only three years. We argue that China's substantial decrease in research productivity is related to diminishing returns to technological catching-up as well as mission-driven policy targeting technological self-sufficiency and national security.
Keywords: 330